2017
DOI: 10.1155/2017/8041647
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Synthesis and Photocatalytic Property of Uranyl Complexes of the β-Diketonates Biscatecholamide Ligand

Abstract: A series of uranyl complexes have been synthesized by reacting hexadentate ligands CH 2 [COO (CH 2 ) n CAM; = 2, 3, 4] 2 [CAM = 2,3-Ph(OH) 2 CONH] containing the catecholamide (CAM) group and -diketonates framework with uranyl nitrate. They were characterized by FTIR, UV-vis, 1 H NMR, XPS, TGA, and elemental analysis. The analysis revealed that oxygen atom of -diketonate did not bind to uranyl ion in complexes 1-3. The photocatalytic degradation properties of the target complexes for degradation of rhodamine B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Recent work has shown that when supported by salen or derivatized catecholate ligands, uranyl ions may assist in the photodegradation of herbicidal viologen-type pollutants. The complexes tested as photocatalysts for RhB destruction were either salicylidene-α-hydroxy acids ([UO 2 (L)­(solv)] (solv = THF ( 245 ) or C 2 H 5 OH ( 246 )), or geometric isomers suggested by the authors to result from the reaction between two asymmetric catecholamides and uranyl nitrate, “[UO 2 (L)]·2H 2 O” ( 247 )); in both cases the uranyl-containing catalysts are poorly defined. , The extent of photocatalytic decomposition of RhB in aqueous solution by 245 and 246 over 3 h is found to be 90% and 70% vs 65–75% for 247 , respectively, with a first-order rate constant for the latter measured as approximately −0.4 s –1 . Both reports invoke de-ethylation of RhB by a *UO 2 2+ electron transfer mechanism, with further oxidative degradation by superoxyl anions, O 2 •– , peroxide radicals, or anion radicals, formed from water or dissolved O 2 .…”
Section: [Uvio2]2+ Photochemical Reactivitymentioning
confidence: 99%
“…Recent work has shown that when supported by salen or derivatized catecholate ligands, uranyl ions may assist in the photodegradation of herbicidal viologen-type pollutants. The complexes tested as photocatalysts for RhB destruction were either salicylidene-α-hydroxy acids ([UO 2 (L)­(solv)] (solv = THF ( 245 ) or C 2 H 5 OH ( 246 )), or geometric isomers suggested by the authors to result from the reaction between two asymmetric catecholamides and uranyl nitrate, “[UO 2 (L)]·2H 2 O” ( 247 )); in both cases the uranyl-containing catalysts are poorly defined. , The extent of photocatalytic decomposition of RhB in aqueous solution by 245 and 246 over 3 h is found to be 90% and 70% vs 65–75% for 247 , respectively, with a first-order rate constant for the latter measured as approximately −0.4 s –1 . Both reports invoke de-ethylation of RhB by a *UO 2 2+ electron transfer mechanism, with further oxidative degradation by superoxyl anions, O 2 •– , peroxide radicals, or anion radicals, formed from water or dissolved O 2 .…”
Section: [Uvio2]2+ Photochemical Reactivitymentioning
confidence: 99%
“…9 In recent years, a rapidly growing range of substrate oxidations are being reported for uranyl nitrate hexahydrate, such as the addition of (cyclo)alkanes to electron-poor olefins, ethers, acetals, and amides arising from hydrogen atom abstraction (HAA) from the hydrocarbon substrate, and other ether and sulfone oxidations. [10][11][12][13][14][15][16][17][18] Uranyl acetate, uranyl sulfate UO2SO4•4H2O, and uranyl triflate UO2(OTf)2•6H2O were all found to give lower yields than uranyl nitrate in those reactions. 6,7,9,18 Uranyl chemistry is dominated by fast ligand exchange between the (normally) five ligands bound in the equatorial plane.…”
Section: Introductionmentioning
confidence: 97%
“…6 A uranyl complex supported by a βdiketonatebis(catecholamide) ligand CH2[COO (CH2)n(2,3-Ph(OH)2CONH)]2 ; n = 3, 4) showed good yields for photocatalytic degradation of rhodamine B. 11 A chiral uranyl salen complex, [UO2(HOEt)(salen)] (salen = 2,2′-((1E,1′E)-((1R,2R)-cyclohexane-1,2-diylbis(azanylylidene))bis-(methanylylidene))diphenol), was used for α-cyanation of anilines. 19 Again, uranyl acetate was found to only give trace amounts of cyanated product.…”
Section: Introductionmentioning
confidence: 99%
“… 6 A uranyl complex supported by a β-diketonatebis(catecholamide) ligand (CH 2 {COO(CH 2 ) n (2,3-Ph(OH) 2 CONH)} 2 ; n = 3, 4) showed good yields for photocatalytic degradation of rhodamine B. 11 A chiral uranyl salen complex, [UO 2 (HOEt)(salen)] (salen = 2,2′-((1 E ,1′ E )-((1 R ,2 R )-cyclohexane-1,2-diylbis(azanylylidene))bis-(methanylylidene))diphenol), was used for α-cyanation of anilines. 21 Again, uranyl acetate was found to only give trace amounts of cyanated product.…”
Section: Introductionmentioning
confidence: 99%
“…9 A rapidly growing range of substrate oxidations is now being reported for uranyl nitrate hexahydrate, include the addition of (cyclo)alkanes to electronpoor olens, ethers, acetals, and amides arising from HAT from the hydrocarbon substrate, ether, sulfone, aniline oxidations, and polymer degradation. [10][11][12][13][14][15][16][17][18][19][20] Uranyl acetate, uranyl sulfate UO 2 SO 4 $4H 2 O, and uranyl triate UO 2 (OTf) 2 $6H 2 O were all found to give lower yields than uranyl nitrate in those reactions. 6,7,9,18 Uranyl chemistry is dominated by fast ligand exchange between the (normally) ve ligands bound in the equatorial plane.…”
Section: Introductionmentioning
confidence: 99%